Coalgebraic Announcement Logics - Gorin, Daniel; Schröder, Lutz; Carreiro, Facundo (Proc. 40th International Colloquium on Automata, Languages, and Programming, ICALP 2013, Part II, 2013)
In epistemic logic, dynamic operators describe the evolution of the knowledge of participating agents through communication, one of the most basic forms of communication being public announcement. Semantically, dynamic operators correspond to transformations of the underlying model. While metatheoretic results on dynamic epistemic logic so far are largely limited to the setting of Kripke models, there is evident interest in extending its scope to non-relational modalities capturing, e.g., uncertainty or collaboration. We develop a generic framework for non-relational dynamic logic by adding dynamic operators to coalgebraic logic. We discuss a range of examples and establish basic results including bisimulation invariance, complexity, and a small model property. © 2013 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.profes_1.coalge_9